Peranan Brand Image dan Customer Experience Terhadap Keputusan Pembelian Ulang pada Produk Skincare Skintific - Soba Evana, Silvia; Arqy Ahmadi, Mirzam (Teewan Journal Solutions, 2025)
The skincare industry in Indonesia has experienced rapid growth as awareness of the importance of skin care increases. Amid fierce competition, Skintific, a Canadian skincare brand that entered the Indonesian market in 2021, seeks to maintain consumer loyalty through effective management of brand image and customer experience. This study aims to analyze the influence of brand image and customer experience on repurchase decisions for Skintific products in Indonesia. Using a qualitative method through a literature review approach, this research gathered secondary data from various relevant scientific sources. The sample consisted of empirical studies related to brand image, customer experience, and repurchase decisions. The results indicate that a positive brand image and satisfying customer experience significantly impact consumer loyalty, leading to repurchase behavior. Findings also highlight that service quality, perceived product value, and customer satisfaction are key factors in fostering consumer loyalty. This study offers insights for companies to design effective marketing strategies to enhance customer loyalty. However, it is limited to literature review analysis and does not include primary data, presenting an opportunity for further research.